Productive role in the financial performance of the banking: An Empirical Study in a sample of Iraqi banks - سعيد, عبد السلام لفته; عباس, علي عبد العزيز (Journal of Economics and Administrative Sciences, 2016)
Abstract :The research aims to study the basic concepts of banking productivity and discuss different approaches to study what ends to identify the most important possible standards applied to measured within the Iraqi banking environment as well as research into the causes of low and high Iraqi banking productivity and identify possible treatments to curb those reasons as to ensure the rise. And in line with the research problem, which states what is the level of productivity and what are the causes of decline and the rise in private banking research sample individually. And what the Iraqi private banks and what is the relationship between performance and the impact of productivity change in the performance of private banks in Iraq. Was the formulation of hypotheses to study and analyze the relationship between the banking sector productivity and financial performance of banks research sample.The research sample determined Sixteen banks from private sector banks, namely, (Bank of Baghdad and the Iraqi Commercial Bank and the Iraqi investment and the Middle East, the Iraqi Investment Bank Bank and United Bank for Investment and the Iraqi Al-Ahli Bank and the Iraqi Credit Bank and Dar es Salaam Investment Bank and the Bank of economy investment and Finance and the Bank of Babylon and Sumer Commercial Bank and Gulf Commercial Bank and Bank of Mosul for Development and Investment and the North Bank for Finance and Investment and Mansour Bank for Investment and Union Bank of Iraq). It has been used Malmquist Malmquist index to extract productivity banking change the values for the period of (2010-2013), in addition to the use of a set of indicators of financial ratios {profitability and liquidity and capital adequacy} for the study of banking performance. Among the most prominent conclusions of the research is that most banks need to improve production performance through the use of available resources and capabilities, as well as by taking advantage of the reduction rates in excess input and output rates of improvement in the stagnant.